Development of a streamlined recombinant protein production and purification protocols from selected bacterial species applicable for biochemical, biophysical and structural analyses - Mohamed Rehan, Aisyah; Md Zin, Noor Hasniza (2016)
Researches using recombinant protein from pathogenic bacterial samples are widely used to understand the biochemistry and processes used by the specific microbes for its viability or ability to evade human host immune system. The specific protein must first be isolated from the bacteria. Cloning the gene encoding the protein, followed by expression and purification in a suitable bacterial host will allow us to obtain a protein purified to suitable level for subsequent biochemical and biophysical experiments. IIUM Kuantan Campus, to the best of our knowledge, does not have a laboratory completely set up for recombinant protein production and purification from bacterial samples. This project aims to develop a suitable laboratory facility and protocol that can be utilized routinely for this purpose. We will clone genes from selected bacterial species with specific known annotated function in a recombinant plasmid; and a fusion tag will be added to help in isolating the protein of interest. Escherichia coli will be used as the bacterial host for expression and purification trials. This project is expected to provide proof of concept for the feasibility of routine cloning, expression and purification of recombinant bacterial protein in our Protein Laboratory suitable for further biochemical, biophysical or structural studies.